2021
DOI: 10.3389/fpsyt.2021.563906
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Psychiatric Emergency and Inpatient Services in the First Month of the Pandemic in a Large Urban Mental Health Hospital in Ontario, Canada

Abstract: The World Health Organization characterized COVID-19 (coronavirus disease 2019) as a pandemic on March 11, 2020 (WHO). Within a couple of days, all Canadian provinces announced the implementation of social distancing measures. We evaluated the immediate effect of COVID-19 on psychiatric emergency and inpatient services in Canada's largest psychiatric hospital in the first month of the pandemic. We extracted data from the electronic medical records of the Center for Addiction and Mental Health in Toronto, Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
(29 reference statements)
1
18
2
Order By: Relevance
“…The overall PEV reduction of 16% during the first COVID-19 wave and 15% during the second wave was substantial. This reduction, however, was not as extensive as in many other studies (8,13,14). For example, a 27% overall reduction in PEVs was observed at an urban hospital in Ontario (12) and a 56% reduction within 2 months during full lockdown in Italy (8).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The overall PEV reduction of 16% during the first COVID-19 wave and 15% during the second wave was substantial. This reduction, however, was not as extensive as in many other studies (8,13,14). For example, a 27% overall reduction in PEVs was observed at an urban hospital in Ontario (12) and a 56% reduction within 2 months during full lockdown in Italy (8).…”
Section: Discussionmentioning
confidence: 81%
“…Acute psychiatric services have been affected during the first wave of the pandemic with a reported 13-56% decrease across countries in adult psychiatric emergency room visits (PEVs) (8)(9)(10)(11)(12)(13)(14)(15). A similar decrease in psychiatric admission rates to inpatient services has been reported between 10 and 41% (13,16,17).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, previous studies highlighted that the number of admissions to psychiatric care facilities showed trends similar to the pre-COVID-19 outbreak period ( 39 ). This result could be due to an adaptation of mental services to give help during the pandemic, especially implementing digital mental health services ( 40 ), while it is in contrast with other findings, e.g., those concerning the decrease of new accesses to psychiatric emergency units ( 41 43 ). Based on the stated above, access to care during the COVID-19 emergency should be further investigated since it represents a complex issue that relies on several possible determinants ( 44 ).…”
Section: Discussionmentioning
confidence: 71%
“…A recent large US cross-sectional study extending until October 2020 showed that at the outbreak of the pandemic, visits for mental health conditions increased in proportion to the decline in overall visits in the ED ( Holland et al, 2021 ). In addition, considering only the initial months of the pandemic may not be sufficient to provide definitive indications about the impact of SARS-CoV-2 on acute psychiatric pathology, as it is known how disastrous events can cause an increase in mental health problems not only in the short term but especially in the long term ( Holland et al, 2021 ; Kim et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%